Symmetrien - Wolschin, Georg (Heidelberger Jahrbücher online, 2019)
Beauty in nature is often – but not always – due to symmetries, structures, or simplicity. Beauty in nature is often – but not always – due to symmetries, structures, or simplicity. Like beauty, simplicity is very hard to grasp or to define in a scientific sense. Structures are much easier to precisely describe and investigate in research projects, such as excellence clusters. In this article, the concept of symmetry, its relation to structures, and the connection to the notion of beauty is explored. Following an introduction about symmetries and structures that we encounter in everyday life, and their impact on our sense of beauty, specific examples from the physical sciences are explored in more detail. The relation between symmetries and conservation laws, as well as their significance for the laws of nature that govern the four fundamental interactions are discussed.